Promoting Active Learning for Increasing Students’ Understanding of the Teaching Materials: A Report on Teaching Experience in Computer Science - Sulistyoningsih, Margaretha (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2020)
Knowledge gap among students is one of the challenges in teaching-learning process. Active learning can be one possible way to the solution, as study shows that active learning increase students’ achievement. Knowledge transfer between peers can have its place in an active class, since group discussion is part of the class design. We have been applying active learning in our classes where students were invited to teach in small groups or in class. In this paper we share about our experience in designing and implementing active learning strategies in our classes. After witnessing students’ success through active learning, we conducted a study to gain students feedbacks about the positive impacts of the active learning to their understanding of the teaching material. Thirty-six students fill out the questionnaire in Google Form anonymously. The result shows that our class settings that employ active learning increases students’ understanding of the teaching materials and hence, students’ grade. Over 93% give positive feedback about our class design and implementation. Students also give positive feedback about our personalized teaching and personal approach during the group activity in our classes. We conclude that class designs which incorporate active learning, is beneficial for students to increase their understanding of the teaching materials.